Endoscopic transposition with the hernial sac (eTHS) in ventral hernia repair - technical description - DA-SILVA,LEONARDO EMILIO (2021)
ABSTRACT Incisional hernia is a late complication of the most frequent after abdominal surgeries, with resulting morbidity that can worsen the condition. The treatment has been done both by open techniques, using screens or not, and by laparoscopic and robotic methods, which use them systematically. However, introducing a permanent foreign body into the tissues requires more surgical time, despite not closing the parietal defect in most cases and a higher risk of infections. New technologies have been trying to improve these results, with absorbable prostheses (biological or synthetic), but their high cost and recurrences remain a severe problem. Even so, standard repair establishes reinforcement with screens, routine, and whether the approach is traditional or mini-invasive. The authors report their first case of endoscopic repair of incisional hernia, which occurred two years ago, with a Brazilian technique already fifty years old: the transposition with the hernia sac proposed by Prof. Alcino Lázaro da Silva in 1971.